High burden of symptoms reported among patients diagnosed with chronic obstructive pulmonary disease (COPD) in Greenland after introducing the COPD Assessment Test in clinical practice - Nielsen, Maja Hykkelbjerg; Lynge, Anna Rask; Pedersen, Michael Lynge (International Journal of Circumpolar Health, 2023)
The aim was to test the internal consistency of the Greenlandic version of the COPD Assessment Test (CAT) questionnaire and to estimate the symptom burden in patients with chronic obstructive pulmonary disease (COPD) in Greenland using the CAT questionnaire. A Greenlandic version of the CAT questionnaire was developed including forward translation, reconciliation, backwards translation, and pilot test. Afterwards, a cross-sectional study of patients with COPD was conducted. The internal consistency assessed by the Cronbach α coefficient was 0.823 for the Greenlandic version of the questionnaire (n = 103). The CAT was negatively correlated to spirometry values and current smoking. In the cross-sectional study (n = 250), 81.1% of the patients experienced a high symptom burden (≥10). The main CAT score was 17 (range 0-38). The CAT was used in 9 out of 17 towns in Greenland. The Greenlandic version of the CAT questionnaire demonstrated a good internal consistency. We observed a high burden of symptoms associated with reduced lung function and active smoking status among patient diagnosed with COPD in Greenland. The questionnaire can be used in clinical practice for assessment of symptom burden in patients with COPD in Greenland and may help to increase focus on symptom control and quality of care.